Modal Interferometer Structures and Splicing Techniques of Fiber Optic Sensor - S, Nur Hidayah; A.R, Hanim; H, Hazura; Zain, A.S.M; Idris, S.K (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This paper discusses the properties of modal interference (MI) for fiber optic sensor (FOS). The performances of the devices had been reviewed based on the structures and the splicing techniques. The structures are based on the standard fibers, polarization maintaining fiber (PMF), photonic crystal fiber (PCF) and fiber Bragg grating (FBG). Meanwhile, the splicing techniques can be categorized as the core mode mismatch, offset splicing, waist enlargement and collapse region. This paper also reports the experimental result of core mode mismatch splicing technique of the SMF-SMF and SMF-MMF-SMF. The response of the power received using various operation wavelengths has been examined. At 1530nm operating wavelength, both structures recorded the highest reading of 59.839uW for SMF-MMF and 62.397uw for SMFMMF-SMF.